Socio-demographic and clinical profile of HIV/AIDS patients attending the ART centre of Amritsar, Punjab - Singh, Amandeep; Mahajan, Sanjeev; Singh, Tejbir; Deepti, Shyam Sunder (International Journal Of Community Medicine And Public Health, 2018)
Background: Due to the large population size, India has the third largest HIV epidemic in the world. There is a need to study the socio-demographic and clinical profile of HIV/AIDS patients for planning services for them. Moreover, it is important to understand the presentation of HIV disease in the local context and culture. There is paucity of studies related to socio-demographic profile of HIV/AIDS patients in Punjab. Methods: This cross sectional study was conducted at anti-retroviral therapy (ART) centre, Government Medical College, Amritsar from January 2016 to December 2016. A total of 400 patients with age more than 18 years and residents of district Amritsar were interviewed by using semi-structured questionnaire. Results: Most of the patients (73.8%) belonged to the age group 41-60 years, 57.75% were males and 42.25% were females. Out of the total patients, 63.8% were married and 29% were widow/widower. There was a predominance of patients from rural areas and from the lower middle and upper lower socio-economic classes. Heterosexual contact was the commonest mode of transmission (66.5%) and felt sick was commonest reason (56.8%) for being tested for HIV. The most common presenting complaints were fever, weakness and weight loss. Conclusions: Majority of patients belonged to low socioeconomic status and productive age group with heterosexual contact being commonest mode of transmission. Females were usually infected secondarily and were diagnosed after the diagnosis of their husband.